“Tightrope walking the twenty-first century”: Jeanette Winterson’s vital connections with Modernism - Marie Laniel (Textes & Contextes, 2012)
In Art Objects (1995), her aesthetic manifesto, Jeanette Winterson calls for a new literature for the new millennium, and new forms of writing that could “answer to twenty-first-century needs”. Far from repudiating the past, Winterson urges the twenty-first-century artist to turn to previous generations for inspiration, and to draw poetic power from the “lineage of art”. Since “every new beginning prompts a return”, before he/she can fully experiment with language, the true artist must first experience his/her vital connections with the past, not in the spirit of ancestor worship, but to reclaim past literature, “(re-state) and (re-instate) (it) in its original vigour”. Striking a delicate balance between continuity and emancipation, responsibility and freedom, the new millennium artist, vitally connected to the past, but in search of his/her own voice, must practice the difficult art of the tightrope walker, uniting two worlds on the “taut line” of language. Because they were able to master this difficult art – breaking new ground, but writing with “generations at (their) back(s)” – it is towards Modernist writers that the new generation must turn for inspiration, and more particularly towards the works of Virginia Woolf. In an attempt to highlight the fruitful tensions between early-twentieth-century and early-twenty-first-century literature, this paper looks at Winterson’s “cover versions” of key Woolfian subtexts, in her works published in the new millennium – The.Powerbook (2000), Lighthousekeeping (2004), The Stone Gods (2007), and her recently published memoir, Why Be Happy When You Could Be Normal? (2011).